PENGARUH PROFITABILITAS DAN DIVIDEN TERHADAP HARGA SAHAM (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF PERIODE 2011-2016) - Aisyah Ratnasari (Jurnal Riset Akuntansi Terpadu, 2018)
The purpose of this study was to determine the effect of Profitability (ROA) and Dividend (DPR) on Stock Prices on Automotive Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange. In this study the data used is secondary data and the methods used are descriptive statistical tests, analysis of the coefficient of determination, simple regression analysis, multiple regression analysis, simple correlation test, and multiple correlation tests. Hypothesis testing with the help of the Statistical Product and Service Solution (SPSS) program version 24. The results of this study are the effect of profitability on stock prices 28.2%, the rest is influenced by other factors as much as 71.8%. Dividend's effect on stock prices is 7.9%, the rest is influenced by other factors as much as 92.1%. the effect of profitability and dividend together on stock prices is 29.8%, the rest is influenced by other factors as much as 70.2%